Prevalence, etiological microorganisms and treatment susceptibility in urinary tract infections in pregnant women of Kohat Khyber Pakhtunkhwa - Heema; Shah, Syed Hasnain Ali; Khawaja, Tariq Mahfooz; Khan, Naimat Ullah; Shinwari, Kausar Rehman; Khan, Saif Ullah (International Journal of Pathology, 2025)
Background: This study aimed to determine the frequency of urinary tract infection (UTI), identify the causative organisms, and assess the antibiotic sensitivity patterns among pregnant women in Kohat. Methods: This cross sectional observational study enrolled 350 pregnant women attending Health Ways Hospital Kohat during December 2024 to April 2025. Midstream clean-catch urine samples were collected and cultured. Positive cultures were further analysed for antimicrobial susceptibility. Socio-demographic characteristics, hemoglobin levels, parity status, trimester of pregnancy, and education levels were also recorded. Data was analysed using SPSS version 22.0. Results: Out of 350 pregnant women aged 18–42 years (mean age 29.84 ± 4.93), 48 (13.7%) were diagnosed with UTI based on positive urine culture. Most cases occurred in the 25–30 age groups. Multiparous women showed a higher prevalence of UTI. A greater proportion of UTI-positive women belonged to low socioeconomic backgrounds and had only primary or secondary education. UTI was more frequent in the third trimester. Escherichia coli (E. coli) were the most common isolated pathogen (45.8%), followed by Klebsiella pneumoniae (18.7%), Pseudomonas (12.5%), Staphylococcus aureus (10.4%), and Enterococcus (10.4%). Highest antibiotic sensitivity was observed for piperacillin-tazobactam (91.7%), meropenem (85.4%), nitrofurantoin (81.2%), and fosfomycin (79.1%). Moderate sensitivity was noted with cefixime, cefotaxime and amoxicillin/clavulanic acid, while high resistance was observed with ampicillin and ciprofloxacin. Conclusion: A notable proportion of pregnant women in Kohat suffered from UTI, with E. coli being the predominant uropathogen. Piperacillin-tazobactum, meropenem, nitrofurantoin, and fosfomycin were the most effective antibiotics. Continuous screening, culture-based diagnosis, and local antibiotic guidelines are necessary to manage UTIs in pregnancy and prevent maternal-fetal complications.